Landslide research : the DST's initiatives - Ramaswamy, S. M., Ed. Singh, Bhoop (New India Publishing Agency, 2017)
The book is a compilation of over 21 Scientific articles on various aspects of Landslides viz: Overviews, Earth system processes and Landslides, Landslide hazard Zonation mapping, Geotechnical investigations, instrumentation and early warning of Landslides, Satellite based monitoring of Landslides, site specific investigations etc.